Preparation, crystallization and X-ray diffraction analysis to 1.5 Å resolution of rat cysteine dioxygenase, a mononuclear iron enzyme responsible for cysteine thiol oxidation - Simmons, Chad R. (International Union of Crystallography, 2005)
Cysteine dioxygenase (CDO; EC 1.13.11.20) is an ∼23 kDa non-heme iron metalloenzyme that is responsible for the oxidation of cysteine by O(2), yielding cysteinesulfinate. CDO catalyzes the first step in the conversion of cysteine to taurine, as well as the first step in the catabolism of cysteine to pyruvate plus sulfate. Recombinant rat CDO was heterologously expressed, purified and crystallized. The protein was expressed as a fusion protein bearing a polyhistidine tag to facilitate purification, a thioredoxin tag to improve solubility and a factor Xa cleavage site to permit removal of the entire N-terminus, leaving only the 200 amino acids inherent to the native protein. A multi-step purification scheme was used to achieve >95% purity of CDO. The optimal CDO crystals diffracted to 1.5 Å resolution and belonged to space group P4(3)2(1)2 or P4(1)2(1)2, with unit-cell parameters a = b = 57.55, c = 123.06 Å, α = β = γ = 90°. CDO shows little homology to any other proteins; therefore, the structure of the enzyme will be determined by ab initio phasing using a selenomethionyl derivative.